Fenomena Arisan Lunas di LPD Desa Adat Gesing - Putu Wahyu Gunawan; Nyoman Ari Surya Darmawan (Jurnal Ilmiah Akuntansi dan Humanika, 2021)
Arisan Lunas is a brand new program that has been started by several Village Kredit Institution (LPD) to earn funding resources from village communities, LPD Desa Adat Gesing is one of the LPDs which implemented the Arisan Lunas program in its business activities. The uniqueness of Arisan Lunas with social gathering in general was, when the participant's number issued in the lottery, all member’s obligations would be completed or they were no need to pay dues for the following month. This topic became interesting to study in order to find out: 1) the Arisan Lunas management system at the LPD Desa Adat Gesing, 2) the prospect for the sustainability of the Arisan Lunas program at the LPD Desa Adat Gesing. In this study used qualitative methods. Data were collected through in-depth interview processes, observation, and documentation study. The results of this study state that: 1) Arisan Lunas LPD Desa Adat Gesing is well managed through clear rules and procedures, in finansial records even though it is not in accordance with generally accepted accounting standards but easily understood by employees, and profit calculations that have been planned by the LPD and 2) seen from the financial and non-financial aspects of the Arisan Lunas LPD Desa Adat Gesing program has a prospect of sustainability.